Teacher Creativity Management In Improving The Quality Of Mathematics Learning - Taufik; Hanafiah; Supyan Sauri (International Journal of Science Education and Technology Management, 2023)
Learning Mathematics is the mother of science, it is unfortunate that this subject is not used as a basis for developing values ​​in building real knowledge and knowledge in the school environment. This study develops Taking a Focus related to "Teacher Creativity Management in improving the Quality of Mathematics Teaching" with the aim of finding a clear picture of this matter. The development of questions presented related to: 1) Planning; 2) Organizing; 3) Implementation; 4) Supervision; 5) Constraints; 6) Efforts; 7) The results of teacher creativity in improving the quality of mathematics learning. with the application of qualitative methods through the development of descriptive analysis and processed through observation, interviews and documentation. Basically applied theory with complexity theory as the basis for problem solving that is built from the results of research where in 1) planning, the limitations of understanding and process standards have not yet determined this. 2) Management management has not been developed yet; 3) The implementation still maintains the established standard pattern; 4) supervision; implementing a tiered supervision pattern; 5) Obstacles in the absence of personnel readiness; 6) efforts to develop a learning system process policy; 7) The results of the development of mathematics learning values ​​have not been developed in an integrated teaching quality. 3) The implementation still maintains the established standard pattern; 4) supervision; implementing a tiered supervision pattern; 5) Obstacles in the absence of personnel readiness; 6) efforts to develop a learning system process policy; 7) The results of the development of mathematics learning values ​​have not been developed in an integrated teaching quality. 3) The implementation still maintains the established standard pattern; 4) supervision; implementing a tiered supervision pattern; 5) Obstacles in the absence of personnel readiness; 6) efforts to develop a learning system process policy; 7) The results of the development of mathematics learning values ​​have not been developed in an integrated teaching quality.